A New Patient with Potocki–Lupski Syndrome: A Literature Review - Praticò, Andrea Domenico; Falsaperla, Raffaele; Rizzo, Renata; Ruggieri, Martino; Verrotti, Alberto; Pavone, Piero (Journal of Pediatric Genetics, 2018)
Speech delay, intellectual disability, and behavioral disturbances are the main clinical manifestations of Potocki–Lupski syndrome. Other features include infantile hypotonia, the absence of major dysmorphism, sleep disorders, and congenital anomalies, particularly of the cardiovascular system. A male patient with Potocki–Lupski syndrome is reported herein. He showed speech and borderline cognitive delay, behavioral troubles with no signs suggestive of autism, in the absence of major dysmorphism. A de novo 17p12-p11.2 duplication spanning 3.6 Mb was detected, with boundaries from 15,284,052 to 18,647,233 (hg19 assembly). At the age of 5 years, the child showed a noticeable improvement of speech skills and a moderate scholastic performance was reached. Upon analysis of the clinical manifestations of the present patient and those reported in existing literature, we found that the syndrome may present in various degrees of clinical expressivity. Affected patients may manifest symptoms ranging from mild behavioral disturbances to severe degrees of autism.
Keywords: Potocki–Lupski syndrome; cognitive delay; autism; behavioral disturbances